Bimbingan dan Konseling sebagai Penyedia Layanan Aktualisasi Diri bagi Peserta Didik - Habsy, Bakharudin All; Adrianti, Ni Kadek Yuanita Adriana; R, Dieni Nur Ilmi Fauziah (Lembaga Yasin AlSys, 2024)
Guidance and Counseling is an effort carried out by an individual who acts as a guide to help individuals achieve optimal potential through various types of services. Guidance and counseling services are provided to individuals with the aim that they can achieve maximum levels of development and happiness in the process of understanding, accepting and adapting to their environment, in accordance with the Guidance and Counseling (BK) function. Along with the aim of guidance and counseling, namely helping individuals plan study achievements, career development and future life, this service is defined by Nurikhsan (2006:15) and is supported by the view that guidance and counseling is a profession that has a responsibility to help students. achieve academic success, career, and personal-social development (Gybers & Handerson, 2000). Therefore, in its services, guidance and counseling is divided into four types of services, namely 1) Academic guidance (learning), 2) Personal-social guidance, 3) Career guidance, and 4) Family guidance. The aim of this research is to assess the significance of guidance and counseling services for students at school in order to optimize their potential. The method used in this research is a qualitative method and literature study.